The Influence of Leading Sectors, Domestic Investment and Population on Regional Original Income (PAD) in Bengkulu Province - Oktaviani. N, Anasthasia; Azansyah, Azansyah (Indonesian Journal of Banking and Financial Technology, 2024)
This research aims to analyze the influence of leading sectors, domestic investment, and population on Regional Original Income (PAD) in Bengkulu Province. Regional economic development is measured through Gross Regional Domestic Product (GRDP), which reflects resource management capabilities and fiscal independence. The data used in this research is secondary data covering the 2019-2023 periode and analyzed using the Location Quotient (LQ) technique and multiple regression methods. The research results show that leading sectors and domestic investment have a significant influence on PAD, while the influence of population varies depending on the sector studied. These findings emphasize the importance of optimizing potential economic sectors and increasing domestic investment to strengthen fiscal independence and regional competitiveness in Bengkulu Province.